Tinjauan Yuridis Keselamatan Dan Keamanan Berlayar Berdasarkan Undang-Undang No. 17 Tahun 2008 Tentang Pelayaran - Aripkah, Nur; Taufik, Muhammad (Langgong: Jurnal Ilmu Sosial dan Humaniora, 2023)
The condition of the ship that is boarded is of course important because if it is neglected, it can have an impact on the security and safety of the passengers. The condition of the ship's cargo that cannot be conditioned often occurs, it can be said that there are no clear provisions regarding the actual cargo of a passenger ship, and the existing supervision is not too strict. On this occasion, the author will discuss the provisions of shipping, especially related to the juridical review of sailing safety and security based on the provisions of Law No. 17 of 2008 concerning Shipping and the principles of legal responsibility for the safety and security of sailing in Law No. 17 of 2008 concerning Shipping. The research method used in this article is normative juridical which is examined by researching primary legal materials and secondary legal materials. The results of the study show that in the provisions of the Shipping Law ships do not just sail away, several maritime requirements must be met, including the safety and security of ships which are part of the ship's seaworthiness. In addition, there are principles of legal responsibility attached to three important elements in sailing, namely the harbor master, skipper, and shipping company.